AI and Creative Writing
X, 182 p. 6 illus., 1 illus. in color.
Keywords: AI and Creative Writing explores the transformations, risks, and possibilities that are brought about by the interaction of artificial intelligence and creative writing. Offering a variety of opinions and thoughts, this book directly considers AI’s impact on our creative writing practices. More generally, it references the impact of AI on types of human knowledge and varieties of human understanding. The focus is on what currently is as well as on what is emerging, while the wider context is the emergence of AI over time, especially since World War II (noting particularly the work of Alan Turing). “AI” in relation to creative writing refers mostly to the training of Large Language Models (LLMs); that is, to the use of chatbots such as ChatGPT. This collection, however, is not so much concerned with specific chatbots. The discussion here is far more about our actions, reactions and expectations, focusing on the ways in which AI and creative writing communicate and might in the future communicate, and why, and to what ends. The result is a stimulating guide to what might or might not be on the horizon for AI’s impact on creative writing. Graeme Harper is Dean of the Honors College and Professor of Creative Writing at Oakland University, USA. He is the author of The Desire to Write (Palgrave, 2019) and editor of the forthcoming Empathy in Creative Writing (Palgrave), among other critical works. An award-winning fiction writer, writing as Brooke Biaz, his works of fiction include Small Maps of the World (2006), Moon Dance (2008), Camera Phone (2009), The Invention of Dying (2015) and The Japanese Cook (2018); Releasing the Animals was published in 2023, and Robots and Other Stories is forthcoming – all from Parlor Press. He is Editor in Chief of New Writing: The International Journal for the Practice and Theory of Creative Writing. It is, however, on AI today and AI in the future that this book focuses – .